Khuda, Falsafiyon Ki Nazar Mein (Maqalaat) - Waheed Ishrat, Dr. (Lahore Sang-e-Meel Publications, 2008)
On God according to Muslim and non Muslim Philosopher, contributed articles.
Keywords: God--History of doctrines -- God (Islam)